(untitled) (Heritage, 2023)
In order to achieve economic progress in less developed countries, it is necessary to provide the necessary resources. Foreign investments very often represent the primary source of financing for certain world economies, and the struggle for financial resources, which are limited, is becoming greater. Many countries have a planned approach to this process, and make huge efforts to attract foreign investors. For this reason, it is necessary to systematically approach this research problem, and to create adequate strategies for attracting foreign investments. When it comes to Bosnia and Herzegovina and the surrounding countries, the competition to attract foreign investments between them is getting tougher. Each of the neighboring countries has its own competitive advantages, and with an adequate set of incentive measures, it can achieve a significant inflow of foreign investments. Unfortunately, of all the surrounding countries, Bosnia and Herzegovina has the lowest inflow of foreign investments, so it is necessary to define the competitive advantages of the business environment in Bosnia and Herzegovina.